Graphite particles, carbon material, and secondary battery

CN122996036APending Publication Date: 2026-10-27MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580023635.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-27
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0030]根据本发明的特定的石墨粒子(A)、以及包含所述石墨粒子(A)和含Si的粒子(B)的负极材料,通过将其用作二次电池的负极活性物质,能提供电池特性优异的二次电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_29
    Figure SMS_29
Patent Text Reader

Abstract

The present invention relates to a graphite particle coated with amorphous carbon, wherein, when the particle is pressurized to a pressure of 9.81 mN and then depressurized to 0.05 mN, the value derived by dividing the amount of displacement of the particle diameter observed when unloaded to 0.05 mN after reaching 9.81 mN by the amount of displacement of the particle diameter when reaching 9.81 mN is 0.5 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to graphite particles, which are excellent battery materials and are used as negative electrode active materials in secondary batteries; carbon materials containing the graphite particles; and secondary batteries using negative electrodes containing the carbon materials. Background Technology

[0002] In recent years, with the miniaturization of electronic devices, the demand for high-capacity rechargeable batteries has gradually increased. In particular, non-aqueous rechargeable batteries, especially lithium-ion batteries, which have higher energy density and excellent fast charge and discharge characteristics compared with nickel-cadmium and nickel-metal hydride batteries, have attracted attention.

[0003] A lithium-ion secondary battery has been developed, consisting of a positive electrode and a negative electrode capable of absorbing / releasing lithium ions, and a non-aqueous electrolyte containing lithium salts such as LiPF6 and LiBF4, for practical use.

[0004] Various negative electrode materials have been proposed as negative electrode materials for this battery. Considering high capacity and excellent flatness of discharge potential, graphitic carbon materials such as natural graphite, coke, artificial graphite obtained by graphitization, graphitized mesophase pitch, and graphitized carbon fibers are used as negative electrode materials.

[0005] Recently, there has been a focus on expanding the applications of non-aqueous secondary batteries, especially lithium-ion secondary batteries. For example, applications are being explored not only in traditional laptops, mobile communication devices, portable cameras, and portable game consoles, but also in power tools and electric vehicles. Therefore, there is a demand for significantly faster charging and discharging capabilities than ever before. Furthermore, there is a desire for lithium-ion secondary batteries with both high capacity and excellent cycle life.

[0006] However, in carbon-centered anodes, the theoretical capacity of carbon is 372 mAh, so capacities exceeding this cannot be expected. Therefore, various anode materials with high theoretical capacities are being investigated, particularly the application of metal particles in anodes (e.g., Patent Document 1).

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2023-156005 Summary of the Invention

[0010] The problem the invention aims to solve

[0011] As in Patent Document 1, it is known that in a lithium-ion battery negative electrode composed of a silicon (Si)-containing active material undergoing volume change, the mechanical properties of the graphite constituting the electrode affect performance. Furthermore, since the Si-containing active material repeatedly expands and contracts during charging and discharging, it is believed that if graphite particles disintegrate during this volume change, it will affect the battery's lifespan. Therefore, a material that can reversibly follow deformation is sought.

[0012] The present invention was made in view of the following technical problem, and the object of the present invention is to provide a graphite material as an electrode constituent material that can reversibly follow the volume change of the active material containing Si in the negative electrode.

[0013] Solution for solving the problem

[0014] The inventors have discovered that by using specific graphite particles, a secondary battery with excellent battery characteristics can be obtained.

[0015] The main points of this invention are as follows.

[0016] Scheme 1 of the present invention is a graphite particle coated with amorphous carbon, wherein the displacement of the particle size observed when the particle is pressurized to a pressure of 9.81 mN and then depressurized to 0.05 mN, divided by the displacement of the particle size when it reaches 9.81 mN, is 0.5 or more.

[0017] Scheme 2 of the present invention is based on the graphite particles of Scheme 1, wherein when the particles are pressurized to a pressure of 9.81 mN, the mechanical curve does not include a plateau region.

[0018] Scheme 3 of the present invention is based on graphite particles according to Scheme 1 or 2, wherein the compressive elastic modulus is 550 MPa or more when the particles are pressurized to a pressure of 9.81 mN.

[0019] Scheme 4 of the present invention is the graphite particles of any one of Schemes 1 to 3, wherein the displacement rate when the particles are pressurized to a pressure of 9.81 mN is less than 10%.

[0020] Solution 5 of the present invention is a carbon material comprising graphite particles according to any one of solutions 1 to 4, wherein the Raman R value of the carbon material is 0.4 or more and 1.0 or less.

[0021] Scheme 6 of the present invention is a carbon material comprising graphite particles according to any one of Schemes 1 to 4, wherein the BET specific surface area of ​​the carbon material is 0.5 m². 2 / g or more and 3.0m 2 / g or less.

[0022] Scheme 7 of the present invention is the graphite particles according to Scheme 1 or 2, wherein the compressive modulus of elasticity when the particles are pressurized to a pressure of 9.81 mN is 150 MPa or more and 300 MPa or less.

[0023] Scheme 8 of the present invention is graphite particles according to Scheme 1, 2 or 7, wherein the displacement rate when the particles are pressurized to a pressure of 9.81 mN is 4% or more and 10% or less.

[0024] Scheme 9 of the present invention is a carbon material comprising graphite particles according to Scheme 1, 2, 7 or 8, wherein the Raman R value of the carbon material is 0.3 or more and 0.4 or less.

[0025] Solution 10 of the present invention is a carbon material comprising graphite particles according to solutions 1, 2, 7 or 8, wherein the BET specific surface area of ​​the carbon material is 0.5 m². 2 / g or more and 3.0m 2 / g or less.

[0026] Scheme 11 of the present invention is a negative electrode material comprising: a carbon material containing graphite particles according to schemes 1 to 4, 7 or 8, and Si-containing particles.

[0027] Solution 12 of the present invention is the negative electrode material according to Solution 11, wherein the negative electrode material further comprises a conductive additive.

[0028] Scheme 13 of the present invention is a secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises graphite particles according to schemes 1 to 4, 7 or 8.

[0029] Invention Effects

[0030] According to the present invention, specific graphite particles (A) and a negative electrode material comprising said graphite particles (A) and Si-containing particles (B) can provide a secondary battery with excellent battery characteristics by using it as a negative electrode active material for a secondary battery. Detailed Implementation

[0031] The present invention will now be described in detail. However, the present invention is not limited to the following description; it can be implemented in any way without departing from the spirit of the invention.

[0032] In this specification, when using "~" and specifying numerical values ​​or property values ​​before and after it, the term is used in a manner that includes the values ​​before and after it. For example, "A~Bμm" means "Aμm or more and Bμm or less". The numerical ranges such as "A~B", "A or more", and "B or less" disclosed in this specification allow for the arbitrary selection of their upper and lower limits.

[0033] "A or above" means "A and / or greater than A", and the numerical range of "greater than A" is also disclosed. Similarly, "below B" means "B and / or less than B", and the numerical range of "less than B" is also disclosed.

[0034] The particle size mentioned in this specification refers to the particle size of the powder as evaluated by volume criterion.

[0035] However, the "particle size of a graphite particle" in the calculation of the compressive elastic modulus of graphite particles is not a statistical value, but refers to the measured value of a single particle.

[0036] In this specification, "d 50 " is the average particle size, set as the median particle size of the volume reference determined by laser diffraction / scattering particle size distribution measurement.

[0037] In this specification, "d 90 "Set as in d" 50 The particle size distribution obtained during the measurement accumulated from the smallest particle side to represent 90% of the particle size.

[0038] In this specification, "d max "Set as in d" 50 The largest particle size of the measured particles is obtained in the particle size distribution during the determination.

[0039] <Graphite Particles (A)>

[0040] One embodiment of the present invention is a graphite particle coated with amorphous carbon, wherein, when the particle is pressurized to a pressure of 9.81 mN and then depressurized to 0.05 mN, the value derived by dividing the particle size displacement observed when the particle is unloaded from 9.81 mN to 0.05 mN by the particle size displacement when the particle reaches 9.81 mN (hereinafter also referred to as the recovery rate) is 0.5 or higher. In this specification, such a graphite particle is also referred to as graphite particle (A).

[0041] From a resilience perspective, the resilience rate is preferably 0.55 or higher, more preferably 0.60 or higher, and even more preferably 0.65 or higher. The graphite particles (A) are preferably particles that do not break under pressure, i.e., graphite particles whose mechanical curve does not include a plateau region when the particles are pressurized to a pressure of 9.81 mN.

[0042] It is known that in lithium-ion battery negative electrodes composed of silicon (Si)-containing active materials with accompanying volume changes, the mechanical properties of the graphite constituting the electrode affect performance. Furthermore, since the Si-containing active materials repeatedly expand and contract during charging and discharging, it is considered that if the graphite particles are damaged during this volume change, it will affect the battery's lifespan. Therefore, a material that reversibly recovers its deformation energy is required.

[0043] The compressive modulus, recovery rate, and displacement rate can be calculated as follows: Using a micro compression testing machine MCT-510 manufactured by Shimadzu Corporation, a graphite particle is pressurized in the vertical direction at a specified load rate. After reaching the maximum test force, the compressive stress and compressive displacement are measured when unloading at a specified unloading rate.

[0044] The compressive modulus can be determined by dividing the compressive stress (= displacement of the particle size at the observation point / particle size of a single graphite particle observed under a microscope before compression) up to the point where the compressive stress reaches 9.81 mN, or up to the point before the plateau is observed in the mechanical curve. The "compressive modulus" in this specification uses the average value of three graphite particles (A) obtained by the method described above.

[0045] The recovery rate can be determined by dividing the displacement of the particle size observed when unloading from 9.81 mN to 0.05 mN by the displacement of the particle size when reaching 9.81 mN. The "recovery rate" in this specification uses the average value of three graphite particles (A) obtained by the method described above.

[0046] The displacement ratio can be determined by dividing the particle size at which it reaches 9.81 mN by the particle size before pressurization. The term "displacement ratio" in this specification uses the average value of three graphite particles (A) obtained by the method described above.

[0047] In one embodiment of the present invention, the particle size of a single graphite particle (A) is preferably 10 μm or more and 25 μm or less, more preferably 12 μm or more and 20 μm or less. The particle size of this single particle is the average of the particle sizes of three graphite particles (A) used in the physical property determination of a single particle.

[0048] Average aspect ratio

[0049] The aspect ratio of the major axis to the minor axis of the graphite particles (A) contained in the carbon material, i.e., the average aspect ratio, is typically 2.1 or more and 10 or less, preferably 2.3 or more and 9 or less, and more preferably 2.5 or more and 8 or less. If the aspect ratio is within the above range, spherical particles can be manufactured efficiently, and tiny voids can be formed within the resulting particles, which can mitigate the volume expansion accompanying charge and discharge and contribute to improved cycle characteristics.

[0050] In this specification, the aspect ratio is calculated as A / B based on the longest diameter A of the particle and the shortest diameter B among the diameters orthogonal to it when observed in three dimensions using a scanning electron microscope. The average aspect ratio is the average of the aspect ratios of any 50 particles.

[0051] Major axis Length of minor axis

[0052] The major axis of the graphite particles (A) is typically 100 μm or less, preferably 90 μm or less, and more preferably 80 μm or less. The minor axis of the graphite particles (A) is typically 0.9 μm or more, preferably 1.0 μm or more, and more preferably 1.2 μm or more. If the major and minor axes of the graphite particles (A) are within the above ranges, tiny voids can easily form within the obtained particles, which can mitigate the volume expansion accompanying charge and discharge and improve cycle characteristics.

[0053] (Types of nuclear graphite)

[0054] In this specification, the material before the graphite particles (A) are coated with amorphous carbon is referred to as nuclear graphite.

[0055] As a core graphite, for example, it can be obtained by removing impurities, crushing, sieving, and classifying artificial graphite made by heating flake, block, or plate-shaped natural graphite, petroleum coke, coal tar pitch coke, coal needle coke, mesophase pitch, etc., to above 2500°C as needed. Among these core graphites, flake, block, or plate-shaped natural graphite is preferred from the perspective of low cost and high capacity, and flake-shaped natural graphite is more preferred.

[0056] Natural graphite is classified according to its properties into flake graphite, crystalline (Vein) graphite, and amorphous graphite (refer to the graphite section of "Integration of Powder and Granular Material Processing Technology" (published by Industrial Technology Center Co., Ltd., 1974) and "HANDBOOKOFCARBON, GRAPHITE, DIAMOND AND FULLERENES" (published by Noyes PubLications)). The degree of graphitization is highest in flake graphite at 100%, followed by flake graphite at 99.9%. Therefore, these types of graphite are preferred.

[0057] Flake graphite, a type of natural graphite, is found in Madagascar, China, Brazil, Ukraine, Canada, and other countries. Lilliform graphite is primarily found in Sri Lanka. Amorphous graphite is mainly found in the Korean Peninsula, China, Mexico, and other regions.

[0058] Among these natural graphites, flake graphite and scaly graphite have advantages such as high graphitization degree and low impurity content, and therefore can be preferred in this invention.

[0059] Examples of visual methods for confirming that graphite is flake-like include: observation of the particle surface using a scanning electron microscope; creating resin sheets by embedding particles in resin and cutting out particle cross-sections, or creating a cross-section of a coating film composed of particles using a cross-section polishing machine, cutting out particle cross-sections, and then observing the particle cross-sections using a scanning electron microscope; etc.

[0060] Flake graphite, including highly purified natural graphite with crystallization methods that closely resemble the crystallinity of graphite, and artificially formed graphite. Among these, natural graphite is preferred because it is soft and easy to create folded structures.

[0061] <Amorphous carbon>

[0062] In one embodiment of the present invention, the graphite particles (A) comprise amorphous carbon. Therefore, they exhibit excellent lithium-ion acceptability.

[0063] Specifically, amorphous carbon can be obtained by heat treatment of the amorphous carbon precursor as described below. The amorphous carbon precursors described in (i) and / or (ii) below are preferred as amorphous carbon precursors.

[0064] (i) Selected organic compounds that can be carbonized from the group consisting of coal-based heavy oil, direct-flow heavy oil, decomposed petroleum heavy oil, aromatic hydrocarbons, N-ring compounds, S-ring compounds, polyphenylene oxide, organic synthetic polymers, natural polymers, thermoplastic resins and thermosetting resins.

[0065] (ii) Amorphous carbon precursors obtained by dissolving carbonizable organic compounds in low-molecular-weight organic solvents.

[0066] (Physical properties of graphite particles (A))

[0067] The preferred properties of the graphite particles (A) in this embodiment are described below. Examples of graphite particles (A) include graphite particles (A1) and (A2) described below.

[0068] Graphite particles (A1)

[0069] If the compressive modulus of elasticity has sufficient strength relative to the volume change of the negative electrode, then the graphite structure is considered to be maintained, affecting the battery's capacity, initial efficiency, and cycle characteristics, thus improving battery life. The compressive modulus of elasticity is increased by the amount of amorphous carbon.

[0070] Therefore, even when using a core of natural graphite with a sufficiently large specific surface area and increasing the amount of amorphous carbon, the compressive modulus can be increased while maintaining capacity by thinning the coating amorphous carbon layer. Methods for increasing the specific surface area of ​​the core graphite include mechanically treating the core graphite to increase its specific surface area, chemically treating it to increase its specific surface area, and granulating and secondary-particle-forming the small-diameter core graphite to increase its specific surface area.

[0071] In graphite particles (A1), the lower limit of the compressive elastic modulus when the particles are pressurized to a pressure of 9.81 mN is preferably 530 MPa or more, more preferably 540 MPa or more, even more preferably 550 MPa or more, and particularly more preferably 560 MPa or more.

[0072] In graphite particles (A1), the upper limit of the compressive modulus when the particles are pressurized to a pressure of 9.81 mN is preferably 800 MPa or less, more preferably 700 MPa or less.

[0073] Among the graphite particles (A1), graphite particles with a displacement rate of less than 10% when the particles are pressurized to a pressure of 9.81 mN are preferred.

[0074] If the displacement rate is too large, the binder used in the electrode will be cut off, and therefore the property of significant shrinkage of graphite particles relative to the volume change of Si is not preferred. Therefore, the aforementioned displacement rate of graphite particles is preferably 1% or more and 10% or less, more preferably 1% or more and 8% or less, and even more preferably 1% or more and 6% or less.

[0075] Graphite particles (A2)

[0076] If the structure exhibits reversibility even with insufficient compressive elastic modulus, it can follow the volume change of the negative electrode, and therefore is believed to have an effect on battery performance. To suppress binder loading, it is believed that as long as the pressure required to operate the electrode containing Si active material is maintained while compressing graphite with a low elastic modulus, binder loading can be suppressed.

[0077] If the amorphous carbon layer becomes thicker, the compressive modulus increases, but it becomes harder and less deformable. If the amorphous carbon layer becomes thinner, although the compressive modulus is lower, the amorphous carbon layer becomes softer, and its conformability is considered to be higher.

[0078] Among the graphite particles (A2), graphite particles with a compressive modulus of 150 MPa or more and 500 MPa or less when the particles are pressurized to a pressure of 9.81 mN are preferred.

[0079] To ensure the most stable operation of the Si-containing electrode, the lower limit of the compressive elastic modulus of the graphite particles is preferably 170 MPa or more, more preferably 190 MPa or more, even more preferably 210 MPa or more, particularly preferably 230 MPa or more, and especially preferably 250 MPa or more. The upper limit of the compressive elastic modulus of the graphite particles is preferably 450 MPa or less, more preferably 400 MPa or less, even more preferably 350 MPa, even more preferably 300 MPa, and especially preferably 280 MPa.

[0080] Among the graphite particles (A2), graphite particles with a displacement rate of 4% or more and 10% or less when the particles are pressurized to a pressure of 9.81 mN are preferred.

[0081] To buffer the volume change of Si, the displacement rate is preferably 4% or more and 10% or less, and more preferably 5% or more and 9% or less.

[0082] (Design method for graphite particles that meet specific mechanical properties)

[0083] In the graphite particles of this embodiment, core graphite coated with amorphous carbon is typically included to improve the acceptance of Li ions.

[0084] The recovery rate of the graphite particles depends on the amount of voids within the particles and the amount of amorphous carbon (hereinafter also referred to as coating). Next, a design policy for graphite particles that meets the specified mechanical properties is considered.

[0085] The amount of voids within the particles can be controlled by the method of manufacturing graphite particles. For example, it can be estimated from the internal pore volume of the manufactured product.

[0086] The coating of amorphous carbon makes the graphite particles rigid, which affects their mechanical properties.

[0087] Generally speaking, increasing the coating amount tends to increase the compressive elastic modulus of graphite particles and decrease the displacement rate.

[0088] Furthermore, if the thickness of the amorphous carbon coating (coating thickness) increases locally, the graphite particles are prone to breakage, which can lead to a decrease in the recovery rate.

[0089] Here, we consider the interface between the liquid amorphous carbon precursor and the coated nucleated graphite surface.

[0090] According to the Wenzel model, the contact angle relative to the nucleated graphite surface decreases as the amount of amorphous carbon precursor increases. However, at the nanoscale, this contact angle is underestimated, and it is assumed that the contact angle becomes extremely large with a given amount of amorphous carbon precursor (e.g., Eric et al., Langmuir 2010 26(16), 13297-13304).

[0091] In this case, the coating thickness becomes higher relative to the amount of amorphous carbon precursor mixed, so it is important to note that it is difficult to meet the desired recovery rate.

[0092] The influence of the contact angle can also be controlled by the interfacial state of the nucleus graphite-amorphous carbon precursor, such as the physical properties of the amorphous carbon precursor and the surface state of the nucleus graphite.

[0093] Therefore, based on the above design guidelines, by adjusting the physical properties of nuclear graphite and amorphous carbon precursors and controlling the coating thickness, graphite particles that meet the desired mechanical properties can be manufactured.

[0094] The following example illustrates the method for calculating the coating thickness.

[0095] First, the coverage coefficient is calculated from the Raman R values ​​of the individual monomers of nuclear graphite, amorphous carbon precursor, and graphite particles.

[0096] Next, based on the surface area of ​​each particle of the nuclear graphite calculated from the specific surface area and average particle size of the nuclear graphite, and the coating amount on the graphite particles, the coating amount of each graphite particle is calculated.

[0097] Furthermore, the total volume of the coating was calculated from the density of amorphous carbon.

[0098] The coating area on a graphite particle is calculated by multiplying the coating rate coefficient by the surface area of ​​each graphite particle. The coating thickness can then be calculated by dividing the total volume of the coated material by the coating area.

[0099] <Carbon Materials>

[0100] Preferred properties of a carbon material comprising graphite particles (A) according to one embodiment of the present invention are as follows. In this specification, the carbon material comprises a plurality of graphite particles (A).

[0101] Average particle size (d50)

[0102] d of carbon materials containing graphite particles (A) 50 Typically, the micrometer size is 1 μm or larger and 120 μm or smaller, preferably 3 μm or larger and 100 μm or smaller, more preferably 5 μm or larger and 90 μm or smaller, and even more preferably 10 μm or larger and 25 μm or smaller. If d50 Within the aforementioned range, when manufacturing anode materials, chromaticity b can be produced by recombination with Si-containing particles (B). Low-density particles. If the carbon material's d... 50 Above the aforementioned lower limit, particles with a particle size range similar to those capable of forming electrodes with a suitable amount of binder can be manufactured. If the d of the carbon material... 50 If the value is below the aforementioned upper limit, then during the manufacturing of secondary batteries, in the process of adding adhesives, water, and organic solvents and coating the particles into a slurry, it is possible to suppress the generation of streaks and unevenness caused by large particles.

[0103] Particle size (d90)

[0104] d of carbon materials containing graphite particles (A) 90 Typically, the micrometer size is 1.5 μm or larger and 150 μm or smaller, preferably 4 μm or larger and 120 μm or smaller, and more preferably 6 μm or larger and 100 μm or smaller. If the carbon material's d... 90 If the value is above the aforementioned lower limit, then the composite of graphite particles (A) and Si-containing particles (B) can be efficiently performed during the manufacture of anode materials. If the d value of the carbon material... 90 If the value is below the upper limit mentioned above, the generation of coarse particles can be suppressed when graphite particles (A) are combined with Si-containing particles (B).

[0105] Particle size distribution

[0106] From the viewpoint of controlling the mechanical properties of carbon materials, the frequency of the particle size of a single graphite particle (A) contained in the carbon material (i.e., the proportion of a single particle (A) that satisfies the specified mechanical properties in the overall carbon material) is preferably 5% or more, more preferably 10% or more, and even more preferably 15% or more. The specified mechanical properties satisfying the embodiments of this invention can be confirmed by attempting to calculate the average value of the properties of a single particle from three randomly selected graphite particles from the carbon material. The "particle size of a single particle" refers to the average value of the average particle sizes of three graphite particles that can be confirmed to satisfy the specified mechanical properties after 10 attempts.

[0107] The frequency of the particle size ±10% of the particle size contained in the carbon material is preferably 20% or more, more preferably 30% or more, and even more preferably 35% or more.

[0108] The frequency of the particle size ±20% of the particle size contained in the carbon material is preferably 40% or more, more preferably 50% or more, even more preferably 55% or more, and particularly more preferably 60% or more.

[0109] Particle size distribution data measured using a laser diffraction / scattering particle size distribution measuring device includes frequencies and cumulative frequencies relative to each particle size. Particle size dn refers to the particle size at which the cumulative frequency is n%.

[0110] For a particle with a diameter dn, the frequency q(dn) is calculated by linear interpolation based on the data of the two nearest points separated by dn (dn1, q(dn1)) and (dn2, q(dn2)).

[0111] For carbon materials containing graphite particles (A), when the pore size distribution measured by mercury porosimetry has two or more peaks, considering the small pore size within the particles, the denser intergranular structure within the particles, and the reduction of electrode expansion, the pore size at the peak of the smallest pore size of the carbon material is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit of the pore size is not particularly limited, but is typically 5 nm or more.

[0112] The cumulative pore volume (mL / g) of the carbon material containing graphite particles (A) is preferably 0.002 to 0.120, more preferably 0.003 to 0.090, even more preferably 0.005 to 0.070, and particularly preferably 0.010 to 0.050. Here, considering the smooth movement of lithium ions within the electrode during charging and discharging, excellent fast charging and discharging characteristics, and superior low-temperature input / output characteristics, it is preferably 0.002 or more, more preferably 0.003 or more, even more preferably 0.005 or more, and particularly preferably 0.010 or more. Furthermore, it is preferably less than 0.120, more preferably less than 0.090, even more preferably less than 0.070, and particularly preferably less than 0.050.

[0113] In this specification, the pore size distribution is determined by mercury porosimetry.

[0114] Specifically, using a mercury porosimeter, a sample weighed to approximately 0.2 g was sealed into a powder sample cell and degassed for 10 minutes at 25°C and below 50 μmHg for pretreatment. Next, the pressure was reduced to 4 psia, and mercury was introduced into the container. The pressure was gradually increased from 4 psia to 40,000 psia, then reduced to 25 psia. The number of pressure increases was set to at least 80 points, and after a 10-second equilibration period in each step, the mercury porosimeter volume was measured. The pore size distribution was calculated using the Washburn equation based on the obtained mercury porosimeter curve. Calculations were performed with a mercury surface tension (γ) of 485 dyne / cm and a contact angle (ψ) of 140°. Based on the results, a graph was plotted with the pore size on the horizontal axis and the pore volume on the vertical axis. From the graph, identify the peaks and the minimum value between the peak with the smallest pore size and the next peak (between the two peaks on the side with the smallest pore size). The cumulative pore volume below this minimum value is taken as the cumulative pore volume (mL / g). A peak represents the apex of the waveform, which is a peak whose height (the difference between the apex and the cumulative pore volumes of the minimum values ​​on both sides) is greater than 0.002 mL / g.

[0115] Tap density

[0116] The tap density of carbon materials containing graphite particles (A) is typically 0.1 g / cm³. 3 Above and 1.0 g / cm 3 The preferred value is 0.13 g / cm³. 3 Above and 0.8g / cm 3 The following is more preferably 0.15 g / cm³. 3 Above and 0.6 g / cm 3 If the tap density is within the above range, tiny voids are easily formed within the resulting particles.

[0117] In this specification, tap density is measured using a powder density meter, when carbon material is filled to a diameter of 1.5 cm and a volume of 20 cm³. 3 After compacting the cylindrical vibratory container, it is compacted 1000 times with a stroke length of 10mm, and the density is calculated based on the volume and mass of the sample at this time.

[0118] In this specification, the specific surface area is a value determined by the BET method based on nitrogen adsorption.

[0119] (002) interplanar spacing (d) 002 ) and Lc

[0120] Interplanar spacing (d) of the (002) plane of a carbon material containing graphite particles (A) based on X-ray wide-angle diffraction. 002The interplanar spacing (d) of the (002) plane is typically above 0.335 nm and below 0.337 nm. For carbon materials, the Lc value based on X-ray wide-angle diffraction is typically above 90 nm, preferably above 95 nm. 002 If the Lc value is below 0.337 nm, it indicates that the graphite particles (A) contained in the carbon material have high crystallinity, which can be used as particles for high-capacity secondary battery negative electrode active materials. Even when the Lc value is above 90 nm, it also indicates that the graphite particles (A) have high crystallinity, which can be used as high-capacity negative electrode active materials.

[0121] In this specification, the interplanar spacing and Lc of the (002) plane are values ​​determined by wide-angle X-ray diffraction.

[0122] Raman R value

[0123] When the graphite particles (A) include the aforementioned graphite particles (A1), the Raman R value of the carbon material is preferably 0.4 or more and 1.0 or less, more preferably 0.4 or more and 0.8 or less, even more preferably 0.4 or more and 0.6 or less, and particularly more preferably 0.4 or more and 0.5 or less.

[0124] The Raman R value can be controlled by the mixing amount of amorphous carbon precursor and the firing temperature.

[0125] When the graphite particles (A) include the graphite particles (A2) described above, the Raman R value of the carbon material is preferably 0.3 or more and 0.4 or less, and more preferably 0.35 or more and 0.4 or less.

[0126] Specific surface area based on BET method

[0127] The preferred BET specific surface area of ​​carbon materials containing graphite particles (A) is 0.5 m². 2 / g or more and 3.0m 2 / g or less, more preferably 1.5m 2 / g or more and 3.0m 2 / g or less.

[0128] <Si-containing particles (B)>

[0129] (Types of Si-containing particles (B))

[0130] The Si-containing particles are included together with the graphite particles of this embodiment in the negative electrode material of this embodiment. Such Si-containing particles are also referred to as Si-containing particles (B). The Si-containing particles (B) only need to contain silicon (Si), which can be elemental Si or a Si compound.

[0131] The Si-containing particles (B) can be in a single crystal or a polycrystalline state. From the viewpoint of easy reduction in particle size and improvement of rate performance, the Si-containing particles (B) are preferably polycrystalline or amorphous.

[0132] Examples of Si compounds include: Si oxides, Si nitrides, and Si carbides.

[0133] Specific Si compounds, when represented by a general formula, include SiOx, SiNx, SiCx, SiZxOy (Z = C, N), etc., with SiOx being the most preferred. The Si compound represented by the general formula SiOx is obtained from silicon dioxide (SiO2) and metallic Si (Si). The value of x is typically 0 or more and 2 or less, preferably 0.1 or more and 1.8 or less, more preferably 0.5 or more and 1.5 or less, and even more preferably 0.8 or more and 1.2 or less. If x is within the above range, it exhibits high capacity while simultaneously reducing irreversible capacity caused by Li-oxygen bonding.

[0134] In this specification, the value of x in SiOx is obtained by determining the oxygen content of SiOx by pulse furnace heating extraction-IR detection under an inert gas atmosphere, determining the silicon content of SiOx by ICP emission spectroscopy, and calculating the ratio of the amount of oxygen to the amount of silicon.

[0135] Compared with carbon materials, SiOx has a larger theoretical capacity. Amorphous Si or nano-sized Si crystals can easily allow the entry and exit of alkaline ions such as lithium ions, resulting in high capacity.

[0136] There are no specific regulations on crystallite size, and impurities may exist within the Si compound and on its surface.

[0137] (Physical properties of Si-containing particles (B))

[0138] Si-containing particles (B) preferably exhibit the following physical properties.

[0139] Average particle size (d50)

[0140] d of Si-containing particles (B) 50 Typically, the particle size is 0.3 μm or more and 10 μm or less, preferably 0.35 μm or more and 3 μm or less, and more preferably 0.4 μm or more and 1 μm or less. If the d of the Si-containing particles (B) 50 Within the above range, the volume expansion during charging and discharging decreases, the charging and discharging capacity can be maintained, and good cycle characteristics can be obtained.

[0141] Specific surface area based on BET method

[0142] The specific surface area of ​​Si-containing particles (B) based on the BET method is typically 0.5 m². 2 / g or more and 120m 2 / g or less, preferably 1m 2 / g or more and 100m 2 / g or less. If the specific surface area of ​​Si-containing particles (B) based on the BET method is within the above range, the battery has high charge and discharge efficiency and discharge capacity, fast lithium inflow and outflow during high-speed charge and discharge, and excellent rate performance, and is therefore preferred.

[0143] oxygen content

[0144] The oxygen content of the Si-containing particles (B) is typically 0.01% by mass or more and 50% by mass or less, preferably 0.05% by mass or more and 45% by mass or less, within 100% by mass of the Si-containing particles (B). The oxygen distribution within the Si-containing particles (B) can exist near the surface, within the particles, or uniformly within the particles, but it is preferred to exist near the surface. If the oxygen content of the Si-containing particles (B) is within the above range, the volume expansion accompanying charge and discharge is suppressed due to the strong bonding between Si and O, resulting in excellent cycle characteristics, and is therefore preferred.

[0145] In this specification, the oxygen content of Si-containing particles (B) is obtained by measuring the oxygen content of Si-containing particles (B) using a pulse furnace heating extraction-IR detection method under an inert gas atmosphere.

[0146] microcrystal size

[0147] The Si-containing particles (B) can have a crystalline structure or be amorphous. When the Si-containing particles (B) have a crystalline structure, the crystallite size of the (111) plane, calculated by X-ray diffraction, is typically 0.05 nm or more and 100 nm or less, preferably 1 nm or more and 50 nm or less. If the crystallite size of the Si-containing particles (B) is within the above range, the reaction between Si and Li ions proceeds rapidly, resulting in excellent input and output, and is therefore preferred.

[0148] In this specification, the crystallite size is determined by the Debye-Scherer method based on the diffraction peaks centered around 2θ=28.4° belonging to the Si(111) plane observed by wide-angle X-ray diffraction.

[0149] (Method for manufacturing Si-containing particles (B))

[0150] The Si-containing particles (B) can be commercially available Si-containing particles. The Si-containing particles (B) can be manufactured by applying mechanical energy to large-sized Si-containing particles using a ball mill or the like, as described later.

[0151] Furthermore, there are no particular restrictions on the manufacturing method. For example, Si-containing particles manufactured by the method described in Japanese Patent No. 3952118 can also be used as Si-containing particles (B).

[0152] For example, in the manufacture of SiOx, silica powder and metallic Si powder are mixed in a specific ratio, the mixture is filled into a reactor, the pressure is reduced to atmospheric pressure or a specific pressure, the temperature is raised to above 1000°C, and the mixture is held to generate SiO gas. Upon cooling, SiO gas is precipitated, yielding SiOx particles of the general formula (vapor deposition). The precipitate can also be processed by applying mechanical energy to form particles, which are then used.

[0153] In the case of mechanical energy processing, for example, by using a ball mill, vibratory ball mill, planetary ball mill, rotary ball mill, bead mill, etc., raw materials and moving bodies that do not react with the raw materials are put into the reactor and subjected to vibration, rotation or a combination of the motions, to form Si-containing particles (B) suitable for one embodiment of the present invention.

[0154] The mechanical energy processing time is typically 3 minutes or more, preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, typically less than 5 hours, preferably less than 4 hours, more preferably less than 3 hours, and even more preferably less than 1 hour. If the mechanical energy processing time is within the above range, both increased productivity and stable product properties can be achieved.

[0155] From a process perspective, the preferred mechanical energy processing temperature is one that is above the solvent's freezing point and below its boiling point.

[0156] The particle size of Si-containing material (B) also depends on the size of the starting material. It is usually prepared by dry grinding using a ball mill, vibratory mill, pulverizer, jet mill, etc., to make it as fine as possible, and then by wet grinding using a bead mill to finally make the particle size uniform. In this wet grinding, it can also be mixed with carbon materials such as carbon black, Ketjen black, acetylene black and used directly.

[0157] In the case of wet milling, the dispersing solvent used is preferably one that has no or very little reactivity with the Si-containing particles (B). If necessary, a trace amount of dispersant (surfactant) may be added to wet the dispersing solvent. The dispersant is also preferably one that has no or very little reactivity with the Si-containing particles (B).

[0158] Types of dispersing solvents

[0159] There are no particular restrictions on the type of dispersion solvent; examples include nonpolar compounds with aromatic rings and polar solvents. As for the types of nonpolar compounds with aromatic rings, there are no particular restrictions, but nonpolar compounds that do not react with Si-containing particles (B) are preferred. Examples include aromatic compounds that are liquid at room temperature such as benzene, toluene, xylene, cumene, and methylnaphthalene; alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, methylcyclohexene, and dicyclohexane; and residual oils from petrochemical and coal chemical processes such as light oils and heavy oils. Among these, xylene, methylnaphthalene, and heavy oils are preferred, with methylnaphthalene and heavy oils being more preferred, and heavy oils being further preferred due to their high boiling points. In wet milling, increasing milling efficiency can easily lead to heat generation. In solvents with low boiling points, this may result in high concentrations due to volatilization.

[0160] As polar solvents, preferred solvents include NMP (N-methyl-2-pyrrolidone), GBL (γ-butyrolactone), DMF (NN-dimethylformamide), methanol, ethanol, 1-propanol, and 2-propanol, which are solvents that can dissolve both water and organic solvents. Among these, NMP (N-methyl-2-pyrrolidone) is preferred from the viewpoint of being less prone to decomposition and having a high boiling point, while 2-propanol is preferred from the viewpoint of low cost.

[0161] The mixing ratio of the dispersion solvent is typically 10% by mass or more and 50% by mass or less, preferably 20% by mass or more and 40% by mass or less, out of a total of 100% by mass of Si-containing particles (B) and dispersion solvent. If the mixing ratio of the dispersion solvent is above or below the aforementioned lower limit, there is a tendency for the dispersion of Si-containing particles (B) to become more uniform. If the mixing ratio of the dispersion solvent is below or below the aforementioned upper limit, there is a tendency for cost reduction.

[0162] Types of dispersants

[0163] A dispersant can be used when manufacturing Si-containing particles (B).

[0164] Examples of dispersants include high molecular weight polyesteramide amines, polyether ester amine salts, polyethylene glycol phosphates, primary to tertiary amines, and quaternary ammonium salts. Among these, high molecular weight polyesteramide amines are preferred from the viewpoint that it is easier to obtain the dispersion effect brought about by steric hindrance.

[0165] <Anode Materials>

[0166] One embodiment of the present invention is an anode material comprising carbon material (A) and Si-containing particles (B).

[0167] (The ratio of carbon material (A) to Si-containing particles (B))

[0168] In one embodiment of the present invention, the preferred proportions of carbon material (A) and Si-containing particles (B) in the negative electrode material are as follows: 10-95% by mass of carbon material (A), 3-60% by mass of Si-containing particles (B), and 100% by mass of carbonaceous material (A), Si-containing particles (B), and any carbonaceous material used as needed; more preferably, 30-90% by mass of carbon material (A) and 5-50% by mass of Si-containing particles (B); and even more preferably, 50-85% by mass of carbon material (A) and 8-40% by mass of Si-containing particles (B). If the proportion of carbon material (A) is above the lower limit and the proportion of Si-containing particles (B) is below the upper limit, it is easier to composite carbon material (A) and Si-containing particles (B). If the proportion of carbon material (A) is below the upper limit and the proportion of Si-containing particles (B) is above the lower limit, then the negative electrode material of one embodiment of the present invention can have high capacity.

[0169] (Conductive additive)

[0170] The negative electrode material preferably further includes a conductive additive. Examples of conductive additives include artificial graphite and carbon nanotubes, which are graphitized by heating carbonaceous materials such as coal tar pitch and resin to above 2500°C. Carbon nanotubes are preferred as conductive additives because they enable effective contact between particles.

[0171] Other physical properties of negative electrode materials

[0172] The preferred properties of the negative electrode material according to one embodiment of the present invention are as follows.

[0173] (002) interplanar spacing (d) 002 )

[0174] The interplanar spacing (d) of the carbon material (A) contained in the negative electrode material of one embodiment of the present invention, based on X-ray wide-angle diffraction, is the (002) plane spacing. 002 The interplanar spacing (d) of the (002) plane is typically 0.335 nm or more and 0.337 nm or less. In one embodiment of the present invention, the Lc of the negative electrode material based on X-ray wide-angle diffraction is typically 90 nm or more, preferably 95 nm or more. If the interplanar spacing (d) of the (002) plane based on X-ray wide-angle diffraction... 002 ) and Lc are particles that are used as negative electrode active materials for secondary batteries to become high-capacity electrodes within the above range.

[0175] Tap density

[0176] In one embodiment of the present invention, the tap density of the negative electrode material is typically 0.5 g / cm³. 3 The above, preferably 0.6 g / cm³ 3 The above, more preferably 0.8 g / cm³ 3 above.

[0177] If the tap density of the negative electrode material in one embodiment of the present invention is above the aforementioned lower limit, the particles are spherical, ensuring sufficient continuous gaps within the electrode, and increasing the mobility of Li ions in the electrolyte within the gaps. This tends to improve rapid charge-discharge characteristics.

[0178] Raman R value

[0179] In one embodiment of the present invention, the Raman R value of the negative electrode material is typically 0.05 or higher and 0.4 or lower, preferably 0.1 or higher and 0.35 or lower. If the Raman R value of the negative electrode material in one embodiment of the present invention is within the above range, the surface crystallinity of the particles is uniform, and high capacity can be expected.

[0180] In this specification, the Raman R value is the value measured at 1580 cm⁻¹ in the Raman spectrum obtained by Raman spectroscopy. -1 The intensity of the nearby peak PA is IA, 1360 cm⁻¹. -1 The intensity IB of the nearby peak PB is calculated as its intensity ratio (IB / IA). "1580cm" -1 "Nearby" refers to 1580-1620cm -1 The range, "1360cm" -1 "Nearby" refers to 1350-1370cm -1 The range.

[0181] Raman spectroscopy can be measured using a Raman spectrometer. Specifically, the sample is filled by allowing the particles to fall naturally into the measuring container, while irradiating the container with an argon ion laser and rotating the container in a plane perpendicular to the laser.

[0182] Specific surface area based on BET method

[0183] The specific surface area of ​​the negative electrode material in one embodiment of the present invention, based on the BET method, is typically 0.1 m². 2 / g or more and 40m 2 / g or less, preferably 0.7m 2 / g or more and 35m 2 / g or less, preferably 1m 2 / g or more and 30m 2 / g or less. If the specific surface area of ​​the negative electrode material according to one embodiment of the present invention based on the BET method is above or above the aforementioned lower limit, there is a tendency for improved lithium-ion acceptance during charging when used as an active material for the negative electrode. If the specific surface area of ​​the negative electrode material according to the BET method according to one embodiment of the present invention is below or above the aforementioned upper limit, when used as an active material for the negative electrode, the reactivity decreases as it suppresses the portion of particles that come into contact with the non-aqueous electrolyte. Therefore, there is a tendency for easier suppression of gas generation and easier acquisition of a preferred battery.

[0184] Average particle size (d) 50 )

[0185] The negative electrode material of one embodiment of the present invention 50 Typically, it is 1 μm or more and 50 μm or less, preferably 4 μm or more and 40 μm or less, and more preferably 6 μm or more and 30 μm or less.

[0186] If the negative electrode material of one embodiment of the present invention is d 50 If the value is above the aforementioned lower limit, particles with a particle size suitable for forming electrodes with an appropriate amount of binder can be manufactured. If the negative electrode material of one embodiment of the present invention has a d... 50 If the value is below the aforementioned upper limit, then during the manufacturing of secondary batteries, in the process of adding adhesives, water, and organic solvents and coating the particles into a slurry, it is possible to suppress the generation of streaks and unevenness caused by large particles.

[0187] <Manufacturing Methods of Carbon Materials>

[0188] There are no particular limitations on the manufacturing method of carbon materials, as long as it can be carried out in a manner that includes graphite particles coated with amorphous carbon and meets the specified mechanical properties. For example, from the perspective of making the pores within the particles dense and effectively controlling the cumulative pore volume, a method of spheroidizing the carbon material raw material in the presence of a granulating agent, pressurizing it, and adding an amorphous carbon precursor is preferred. Specifically, a manufacturing method including the following steps (1) to (6) is preferred.

[0189] Process (1): The process of adjusting the particle size of carbon material raw materials.

[0190] Process (2): The process of mixing carbon material raw materials with granulating agent.

[0191] Process (3): The process of spheroidizing carbon material raw materials.

[0192] Process (4): The process of removing the granulating agent.

[0193] Process (5): Pressure treatment process.

[0194] Process (6): The process of adding amorphous carbon.

[0195] The following describes the processes (1) to (6), but processes other than those (1) to (6) may be included before and after each process, and the manufacturing method is not limited to those including processes (1) to (6).

[0196] (Process (1))

[0197] Process (1) is the process of adjusting the particle size of carbon material raw materials.

[0198] The raw material for carbon materials is graphite. Considering high crystallinity and excellent capacity, natural graphite and artificial graphite are preferred. Considering even higher crystallinity, superior capacity, and the fact that no heat treatment is required during manufacturing, natural graphite is preferred. Graphite with fewer impurities is preferred, and it is preferable to use it after purification treatment as needed.

[0199] (Process (2))

[0200] Process (2) is the process of mixing carbon material raw materials with granulating agent.

[0201] The granulating agent is preferably a liquid when spherizing carbon material raw materials.

[0202] Furthermore, the granulating agent preferably contains an organic compound that becomes amorphous carbon.

[0203] Furthermore, the granulating agent is preferably a granulating agent that does not contain organic solvents, a granulating agent that contains organic solvents and at least one of the organic solvents does not have a flash point, or a granulating agent that contains organic solvents with a flash point of 5°C or higher.

[0204] When the granulating agent meets the above necessary conditions, it becomes a liquid bridge between the carbon material raw materials during the spheroidization process. The capillary negative pressure of the liquid bridge and the surface tension of the liquid generate attraction between the carbon material raw materials, which can effectively shorten the distance between the carbon material raw materials.

[0205] (Process (3))

[0206] Process (3) is a process of spheroidizing carbon material raw materials.

[0207] As a method for spheroidizing carbon material raw materials, considering the ease of controlling the particle shape, the method of spheroidizing carbon material raw materials by imparting mechanical energy is preferred.

[0208] Examples of mechanical energy include impact, compression, friction, and shear force. These mechanical energies can be used individually or in combination.

[0209] The method of spherizing carbon raw materials by imparting mechanical energy can be achieved simply by using a device that applies mechanical energy.

[0210] When spheroidizing carbon material raw materials, it is preferable to perform the spheroidizing process while simultaneously adhering the microparticles generated during the spheroidizing process to the surface of the carbon material. By performing the spheroidizing process while simultaneously adhering the microparticles generated during the spheroidizing process to the surface of the carbon material, the porosity within the carbon material can be effectively reduced when coating the carbon material with amorphous carbon or graphitic materials. Furthermore, the amount of edges that can be utilized as lithium ion insertion and extraction sites increases, making it easier for the electrolyte to effectively distribute throughout the porosity of the carbon material.

[0211] Micronized powder can be produced not only during the spheroidization process, but also by adding micronized powder with adjusted particle size.

[0212] In order to enable the micro powder to adhere effectively to the surface of carbon materials, it is preferable to enhance the adhesion between carbon material particles, between carbon material particles and micro powder particles, and between micro powder particles.

[0213] As a form of adhesion between particles, examples include: van der Waals forces and electrostatic attraction without the aid of interparticle inclusions; and physical cross-linking forces and chemical cross-linking forces with the aid of interparticle inclusions.

[0214] The particle size of carbon materials can be controlled by the spheroidization process time and the amount of mechanical energy imparted.

[0215] Carbon material raw materials and granulating agents can also be added to the spheroidizing treatment device, and processes (2) and (3) can be carried out simultaneously.

[0216] (Process (4))

[0217] Step (4) is the process of removing the granulating agent.

[0218] Granulators can remove all or part of the granules.

[0219] When using granulating agents containing organic solvents, it is preferable to also remove the organic solvents.

[0220] Methods for removing granulating agents and organic solvents include, for example, methods using solvents for cleaning and methods that cause them to evaporate / decompose by heating. Among these methods, the method of causing them to evaporate / decompose by heating is preferred from the perspective of superior productivity and removal efficiency.

[0221] (Process (5))

[0222] Process (5) is the process of pressurizing.

[0223] As a type of pressurization treatment, examples include isotropic pressurization treatment and anisotropic pressurization treatment.

[0224] As a pressurization method, isotropic pressurization is preferred, such as hydrostatic isotropic pressurization using water as the pressurization medium, gas pressure-based isotropic pressurization using air or other gases as the pressurization medium, and pressurization by filling into a mold and pressing along a fixed direction by uniaxial pressing.

[0225] The pressure applied is preferably 50 to 300 MPa, more preferably 100 to 280 MPa, and even more preferably 150 to 260 MPa. Here, from the viewpoint of easily controlling the pressure so that the obtained carbon material (A) satisfies formula (1), the pressure applied is preferably 50 MPa or more, more preferably 100 MPa or more, even more preferably 150 MPa or more, and even more preferably 300 MPa or less, more preferably 280 MPa or less, and even more preferably 260 MPa or less.

[0226] Step (5) can be performed at any point in time between steps (1) and (6), but from the perspective of effectively pressurizing after removing excess granulating agent, it is preferable to perform it between steps (4) and (6).

[0227] (Process (6))

[0228] Process (6) is the process of adding amorphous carbon.

[0229] By adding amorphous carbon to carbon materials, side reactions between the negative electrode and the electrolyte can be suppressed.

[0230] Amorphous carbon refers to d 002 Carbon with a value of 0.340 nm or higher.

[0231] From the perspective of easily controlling the amount of voids within the particles, the preferred method for adding amorphous carbon to carbon materials is to mix the carbon material with an amorphous carbon precursor, heat it in a non-oxidizing atmosphere, and then carbonize the amorphous carbon precursor into an amorphous form.

[0232] The mixing ratio of carbon material and amorphous carbon precursor can be appropriately set to achieve the desired coating rate.

[0233] There are no particular limitations on the atmosphere during heating, as long as it is a non-oxidizing atmosphere. From the perspective of suppressing the formation of micropores caused by oxidation, nitrogen, argon, or carbon dioxide are preferred, and nitrogen is more preferred.

[0234] The heating temperature for amorphous carbonization of the amorphous carbon precursor is not particularly limited as long as it does not reach a temperature equivalent to the crystal structure of graphite. Preferably, it is 500–2000°C, more preferably 600–1800°C, and even more preferably 700–1600°C. Here, the aforementioned heating temperature is preferably 500°C or higher, more preferably 600°C or higher, and even more preferably 700°C or higher. Furthermore, it is preferably 2000°C or lower, more preferably 1800°C or lower, and even more preferably 1600°C or lower.

[0235] Examples of amorphous carbon precursors include aromatic hydrocarbons such as tar, pitch, naphthalene, and anthracene, as well as thermoplastic resins such as phenolic resins and polyvinyl alcohol resins. These precursors can be used individually or in combination of two or more. Among these precursors, tar, pitch, and aromatic hydrocarbons are preferred from the perspective of ease of carbon structure development and the ability to be coated with a small amount of carbon.

[0236] The amount of amorphous carbon precursor mixed with the heating temperature can be used to control the amount of amorphous coating and the Raman R value of the carbon material.

[0237] In order to ensure that the volume-based average particle size of the carbon material is within the desired range, the carbon material obtained through processes (1) to (6) can be crushed, broken, and graded as needed.

[0238] Crushing, breaking, and grading can be done using well-known methods.

[0239] <Manufacturing Methods of Anode Materials>

[0240] The method for manufacturing the negative electrode material in this embodiment includes a step of mixing carbon material (A) with Si-containing particles (B). A conductive additive may also be mixed in this process. The mixing method is not particularly limited as long as it allows the carbon material (A) and Si-containing particles (B) to be mixed in a manner that results in the desired composition.

[0241] <Application>

[0242] The negative electrode material of one embodiment of the present invention, when used as a negative electrode active material in a secondary battery, enables the realization of a secondary battery with excellent battery characteristics. Therefore, the negative electrode material of one embodiment of the present invention is useful as a negative electrode active material in a secondary battery.

[0243] [Secondary battery]

[0244] One embodiment of the present invention provides a secondary battery comprising a positive electrode, a negative electrode, and an electrolyte. The negative electrode comprises a current collector and a negative electrode active material layer formed on the current collector, the negative electrode active material layer comprising the negative electrode material of one embodiment of the present invention. The secondary battery of one embodiment of the present invention is typically manufactured by a method for manufacturing a secondary battery according to one embodiment of the present invention, the method comprising the step of forming a negative electrode active material layer comprising the negative electrode material of one embodiment of the present invention on the current collector to obtain the negative electrode.

[0245] <Negative electrode>

[0246] When a negative electrode (hereinafter sometimes referred to as "the negative electrode of one embodiment of the present invention") is made by using the negative electrode material of one embodiment of the present invention, a material containing a binder (adhesive resin) in the negative electrode material of one embodiment of the present invention is dispersed in a dispersion medium to form a slurry, which is then coated onto a current collector and dried to form a negative electrode active material layer on the current collector.

[0247] As an adhesive, adhesives with intramolecular olefinic unsaturated bonds are used. There are no particular limitations on their types. Specific examples include styrene-butadiene rubber and styrene... Isoprene Styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene propylene Diene copolymers, etc. By using such adhesives with olefinically unsaturated bonds, the swelling of the negative electrode active material layer to the electrolyte can be reduced. Among these, styrene-butadiene rubber is preferred due to its ease of acquisition.

[0248] As an adhesive with intramolecular olefinic unsaturated bonds, adhesives with large molecular weight or high proportion of unsaturated bonds are preferred.

[0249] As a high molecular weight adhesive, its weight-average molecular weight is typically 10,000 or more, preferably 50,000 or more, and generally below 1 million, preferably below 300,000. As a high proportion of unsaturated bonds, it is desirable that the molar number of olefinic unsaturated bonds per 1g of total adhesive is typically 2.5 × 10⁻⁶. -7 The preferred value is 8×10. -7 The above, in addition, is usually 5×10 -6 The following is preferred at 1×10 -6 Within the following range.

[0250] As an adhesive, it is sufficient to satisfy at least one of the requirements related to molecular weight and the requirements related to the proportion of unsaturated bonds, but it is more preferable to satisfy both requirements simultaneously. If the molecular weight of the adhesive with olefinic unsaturated bonds is too small, the mechanical strength is poor. If the molecular weight of the adhesive is too large, the flexibility is poor. Furthermore, if the proportion of olefinic unsaturated bonds in the adhesive is too low, the strength-enhancing effect is weak; if it is too high, the flexibility is poor.

[0251] The degree of unsaturation of adhesives containing olefinic unsaturated bonds is typically 15% or more, preferably 20% or more, more preferably 40% or more, typically 90% or less, and preferably 80% or less. The degree of unsaturation represents the proportion (%) of the double bond relative to the repeating unit of the polymer.

[0252] Adhesives without olefinic unsaturated bonds can also be used in combination with the aforementioned adhesives containing olefinic unsaturated bonds, without sacrificing the effects of the present invention. The mixing ratio of the amount of adhesive without olefinic unsaturated bonds to the amount of adhesive containing olefinic unsaturated bonds is typically 150% by mass or less, preferably 120% by mass or less.

[0253] Coating properties can be improved by using adhesives that do not have olefinic unsaturated bonds, but if too much is used, the strength of the active material layer will be reduced.

[0254] Examples of adhesives that do not have olefinic unsaturated bonds include polysaccharides such as methylcellulose, carboxymethylcellulose, and starch; thickening polysaccharides such as carrageenan, pullulan, guar gum, and xanthan gum; polyethers such as polyethylene oxide and polypropylene oxide; vinyl alcohols such as polyvinyl alcohol and polyvinyl butyral; polyacids or metal salts of these polymers such as polyacrylic acid and polymethyl methacrylate; fluorinated polymers such as polyvinylidene fluoride; alkane polymers such as polyethylene and polypropylene, and their copolymers.

[0255] The mass ratio (anode material / binder) of the slurry to the binder (as described above, which may be a mixture of binder with unsaturated bonds and binder without unsaturated bonds) is typically 90 / 10 or more, preferably 95 / 5 or more, typically 99.9 / 0.1 or less, and preferably 99.5 / 0.5 or less, on a dry basis.

[0256] If the proportion of binder is too high, it can easily lead to a decrease in capacity and an increase in resistance. If the proportion of binder is too low, the strength of the negative electrode plate will be weakened.

[0257] As a dispersion medium for preparing slurries containing negative electrode materials and binders, organic solvents such as ethanol and water can be used.

[0258] Conductive agents can also be added to the slurry as needed. Examples of conductive agents include carbon blacks such as acetylene black, Ketjen black, and furnace black, as well as micro powders composed of Cu, Ni, or their alloys with a particle size of less than 1 μm. The amount of conductive agent added is typically less than 10% by mass relative to the negative electrode material.

[0259] The current collector for coating the slurry can be any conventionally known current collector. Specifically, examples include rolled copper foil, electrolytic copper foil, stainless steel foil, and other metal films. The thickness of the current collector is typically 4 μm or more, preferably 6 μm or more, typically 30 μm or less, and preferably 20 μm or less.

[0260] The above-mentioned slurry is applied to the current collector using a scraper or similar tool and allowed to dry. Then, it is pressed using a roller press to form a negative electrode active material layer. At this point, it is preferable that the amount of negative electrode material adhering to the current collector is 5–15 mg / cm³. 2 The slurry is applied in a specific manner.

[0261] The drying of the slurry after it is applied to the current collector is usually carried out at a temperature above 60°C, preferably above 80°C, usually below 200°C, preferably below 195°C, in dry air or an inert atmosphere.

[0262] The thickness of the negative electrode active material layer obtained by coating and drying the slurry is typically 5 μm or more, preferably 20 μm or more, more preferably 30 μm or more, typically 200 μm or less, preferably 100 μm or less, and more preferably 75 μm or less in the pressed state. If the negative electrode active material layer is too thin, its practicality as a negative electrode active material layer is insufficient, considering both the particle size of the negative electrode material itself and the material's properties. If the negative electrode active material layer is too thick, it is difficult to obtain sufficient Li ion adsorption / release for high-density current values.

[0263] The density of the negative electrode material in the negative electrode active material layer varies depending on the application; for applications where capacity is important, a density of 1.55 g / cm³ is preferred. 3 The above, especially preferred, is 1.6 g / cm³. 3 The above is further optimized to 1.65 g / cm³. 3 The above, especially preferred, is 1.7 g / cm³. 3 The above applies. If the density is too low, the capacity per unit volume of battery may not be sufficient. If the density is too high, the rate capability will decrease. Therefore, the preferred density of graphite is 1.9 g / cm³. 3 the following.

[0264] When using the negative electrode material described above to fabricate the negative electrode of one embodiment of the present invention, there are no particular limitations on the method or the selection of other materials.

[0265] When using this negative electrode to make a secondary battery, there are no particular restrictions on the selection of components required for the battery structure, such as the positive electrode and electrolyte.

[0266] Secondary batteries

[0267] The following description, using a lithium-ion secondary battery as an example, details a secondary battery according to one embodiment of the present invention, which includes a negative electrode using a negative electrode material. The materials and manufacturing methods that can be used in the secondary battery according to one embodiment of the present invention are not limited to the specific examples described below.

[0268] The basic structure of a secondary battery, particularly a lithium-ion secondary battery, according to one embodiment of the present invention is the same as that of conventionally known lithium-ion secondary batteries, typically including a positive electrode, a negative electrode, and an electrolyte capable of absorbing / releasing lithium ions. The negative electrode described above, according to one embodiment of the present invention, is used as the negative electrode.

[0269] The positive electrode is formed by forming a layer of positive electrode active material containing positive electrode active material and binder on the current collector.

[0270] As positive electrode active materials, examples include metal chalcogenides that can absorb and release alkali metal cations such as lithium ions during charging and discharging. Examples of metal chalcogenides include transition metal oxides such as vanadium oxides, molybdenum oxides, manganese oxides, chromium oxides, titanium oxides, and tungsten oxides; transition metal sulfides such as vanadium sulfides, molybdenum sulfides, titanium sulfides, and CuS; phosphorus-sulfur compounds of transition metals such as NiPS3 and FePS3; selenium compounds of transition metals such as VSe2 and NbSe3; and Fe... 0.25 V 0.75 S2, Na 0.1 Composite oxides of transition metals such as CrS2; composite sulfides of transition metals such as LiCoS2 and LiNiS2, etc.

[0271] Among these, V2O5 and V5O are preferred. 13 , VO2, Cr2O5, MnO2, TiO, MoV2O8, LiCoO 2、 LiNiO2, LiMn2O4, TiS2, V2S5, Cr 0.25 V 0.75 S2, Cr 0.5 V 0.5 S2, etc., with LiCoO2 and LiNiO being particularly preferred. 2、 LiMn2O4 is a lithium transition metal composite oxide obtained by replacing some of these transition metals with other metals. These positive electrode active materials can be used alone or in combination.

[0272] As a binder for the positive electrode active material, any known binder can be used. Examples include inorganic compounds such as silicates and water glass, resins without unsaturated bonds such as Teflon (registered trademark) and polyvinylidene fluoride. Among these, resins without unsaturated bonds are preferred. If a resin with unsaturated bonds is used as the binder for the positive electrode active material, it may decompose during the oxidation reaction (charging). The weight-average molecular weight of these resins is typically 10,000 or more, preferably 100,000 or more, typically 3 million or less, and preferably 1 million or less.

[0273] To improve the conductivity of the electrode, the positive electrode active material layer may contain a conductive agent. There are no particular restrictions on the conductive agent, as long as it can be appropriately mixed with the active material to impart conductivity. Common examples of conductive agents include acetylene black, carbon black, carbon powders such as graphite, and fibers, powders, and foils of various metals.

[0274] The positive electrode plate is formed by using the same method as the negative electrode in one embodiment of the present invention described above, by slurrying the positive electrode active material and binder with a dispersant, coating it onto the current collector, and drying it. The current collector for the positive electrode can be made of aluminum, nickel, stainless steel (SUS), etc., without any limitation.

[0275] As an electrolyte, non-aqueous electrolytes can be used, which are formed by dissolving lithium salts in non-aqueous solvents, or electrolytes that are made into gel-like, rubber-like, or solid sheet-like forms by using organic polymers.

[0276] There are no particular restrictions on the non-aqueous solvents used in non-aqueous electrolytes; appropriate selections can be made from well-known non-aqueous solvents that have been previously used as solvents for non-aqueous electrolytes. Examples include chain carbonates such as diethyl carbonate, dimethyl carbonate, and methyl ethyl carbonate; cyclic carbonates such as ethylene carbonate, propylene carbonate, and butyl carbonate; chain ethers such as 1,2-dimethoxyethane; cyclic ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, sulfolane, and 1,3-dioxolane; chain esters such as methyl formate, methyl acetate, and methyl propionate; and cyclic esters such as γ-butyrolactone and γ-valerolactone.

[0277] These non-aqueous solvents can be used individually or in mixtures of two or more. In the case of mixed solvents, a combination of mixed solvents containing cyclic carbonates and chain carbonates is preferred. The cyclic carbonate is a mixture of ethylene carbonate and propylene carbonate, which is particularly preferred from the viewpoint that it exhibits high ionic conductivity even at low temperatures and improved low-temperature charge load characteristics.

[0278] The content of propylene carbonate relative to the total content of the non-aqueous solvent is preferably in the range of 2% by mass or more and 80% by mass or less, more preferably in the range of 5% by mass or more and 70% by mass or less, and even more preferably in the range of 10% by mass or more and 60% by mass or less. If the content of propylene carbonate is lower than the above lower limit, the ionic conductivity at low temperature decreases. If the content of propylene carbonate is higher than the above upper limit, the following problem exists: propylene carbonate solvated with Li ions is co-inserted into the graphite phase of the negative electrode, thereby causing interlayer delamination and deterioration of the graphite-based negative electrode active material, resulting in insufficient capacity.

[0279] There are no particular restrictions on the lithium salts used in non-aqueous electrolytes; appropriate selections can be made from well-known lithium salts known to be suitable for this application. Examples include: halides such as LiCl and LiBr; perhalates such as LiClO4, LiBrO4, and LiClO4; inorganic lithium salts such as inorganic fluoride salts such as LiPF6, LiBF4, and LiAsF6; perfluoroalkane sulfonates such as LiCF3SO3 and LiC4F9SO3; and fluorinated organic lithium salts such as perfluoroalkane sulfonylimide salts such as lithium trifluorosulfonylimide ((CF3SO2)2NLi). Among these, LiClO4, LiPF6, and LiBF4 are preferred.

[0280] Lithium salts can be used alone or in mixtures of two or more. The concentration of lithium salts in non-aqueous electrolytes is typically in the range of 0.5 mol / L or higher and 2.0 mol / L or lower.

[0281] When the aforementioned non-aqueous electrolyte contains organic polymers and is formulated into gel, rubber, or solid sheet form for use as an electrolyte, specific examples of organic polymers include: polyether-based polymers such as polyethylene oxide and polypropylene oxide; cross-linked polymers of polyether-based polymers; vinyl alcohol-based polymers such as polyvinyl alcohol and polyvinyl butyral; insolubles of vinyl alcohol-based polymers; polyepoxychloropropane; polyphosphazene; polysiloxane; vinyl-based polymers such as polyvinylpyrrolidone, polyvinyl carbonate, and polyacrylonitrile; and polymer copolymers such as poly(ω-methoxyloxyethylene methacrylate), poly(ω-methoxyloxyethylene methacrylate-co-methyl methacrylate), and poly(hexafluoropropylene-vinylidene fluoride).

[0282] The aforementioned non-aqueous electrolyte may also contain a film-forming agent. Specific examples of film-forming agents include: carbonate compounds such as vinylene carbonate, vinyl ethyl carbonate, and methyl phenyl carbonate; olefin sulfides such as ethylene sulfide and propylene sulfide; sulcinolone compounds such as 1,3-propane sulcinolone and 1,4-butane sulcinolone; and acid anhydrides such as maleic anhydride and succinic anhydride.

[0283] Furthermore, overcharge preventers such as diphenyl ether and cyclohexylbenzene can be added to non-aqueous electrolytes.

[0284] When using these additives, their content in the non-aqueous electrolyte is typically 10% by mass or less, preferably 8% by mass or less, more preferably 5% by mass or less, and particularly preferably 2% by mass or less. Excessive content of these additives may adversely affect other battery characteristics such as the increase in initial irreversible capacity, low-temperature performance, and rate capability.

[0285] As an electrolyte, a polymeric solid electrolyte that acts as a conductor of alkali metal cations such as lithium ions can also be used. Examples of polymeric solid electrolytes include those based on the aforementioned polyether system.

[0286] Polymer solid electrolytes containing dissolved Li salts in molecular compounds, and polymers in which the terminal hydroxyl groups of polyethers are replaced by alkoxides, etc.

[0287] Typically, to prevent short circuits between electrodes, a porous membrane, such as a porous membrane or non-woven fabric, is sandwiched between the positive and negative electrodes. In this case, a non-aqueous electrolyte is impregnated within the porous membrane for use. Polyolefins such as polyethylene and polypropylene, and polyethersulfone, are used as membrane materials, with polyolefins being preferred.

[0288] There are no particular limitations on the form of the lithium-ion secondary battery using the present invention. Examples include a cylindrical type with a spiral-shaped sheet electrode and separator, a cylindrical type with an inner and outer structure formed by combining a particle electrode and separator, and a coin type formed by stacking a particle electrode and separator.

[0289] By storing these batteries in any type of outer casing, they can be made into any shape, such as coin-shaped, cylindrical, or square, for use.

[0290] There are no particular restrictions on the assembly process of lithium-ion secondary batteries; they can be assembled using an appropriate process based on the battery's structure. For example, the negative electrode can be placed on the outer casing, with the electrolyte and separator placed on top of it, and the positive electrode placed opposite the negative electrode. The battery is then riveted together with gaskets and sealing plates to form a battery.

[0291] Example

[0292] The present invention will be further described in detail below based on embodiments. It should be noted that the present invention is not limited to the following embodiments.

[0293] Based on the description in "(Design Method for Graphite Particles Satisfying Specific Mechanical Properties)," particle design is performed assuming spherical shapes. It should be noted that the Raman R value of nucleated graphite is 0.25, the Raman R value of amorphous carbon is 1.05, and the density of nucleated graphite is assumed to be 2.2 g / cm³. 3 The density of graphite particles is assumed to be 2.1 g / cm³. 3 The coating coefficient is defined by standardizing the respective R values. The mixing amount of the amorphous carbon precursor is optimized in a manner that results in a specified coating thickness.

[0294] (Comparative Example 1)

[0295] In flake graphite (volume-based average particle size: 11.1 μm, d 90 Micrometer diameter: 21.1 μm, Specific surface area: 9.9 m² 2 / g, tap density: 0.44g / cm³ 3 A granulating agent was added to the mixture, and it was stirred and mixed using a stirring granulator. The resulting mixture was fed into a hybrid system and subjected to mechanical granulation and spheroidization at a rotor circumferential speed of 85 m / s for 5 minutes. The granulating agent was then removed by heat treatment to obtain spherical graphite particles. The obtained spherical graphite particles were filled into a rubber container, sealed, and subjected to isotropic pressurization followed by crushing / grading to obtain core graphite. The obtained spherical graphite particles and pitch (ash content: 0.02 wt%, metal impurity content: 20 ppm wt%, Qi: 1 wt%) were mixed to meet specified mechanical properties and heat-treated at 1300°C in an inert gas atmosphere to obtain a calcined product. The calcined product was crushed / graded to obtain the carbon material containing graphite particles of Example 1.

[0296] (Example 1)

[0297] The carbon material containing graphite particles of Comparative Example 1 was prepared by increasing the content of amorphous carbon relative to 100% by mass of the calcined product and mixing spherical graphite particles with pitch, otherwise proceeding in the same manner as in Example 1.

[0298] (Comparative Example 2)

[0299] The content of amorphous carbon relative to 100% by mass of the calcined product was increased compared to Example 1, and spherical graphite particles were mixed with pitch. Otherwise, the same procedure as in Example 1 was followed to produce a carbon material containing graphite particles, as in Comparative Example 2.

[0300] (Example 2)

[0301] The content of amorphous carbon relative to 100% by mass of the calcined product was increased in Comparative Example 2, and spherical graphite particles were mixed with pitch. Otherwise, the same procedure as in Example 1 was followed to produce the carbon material containing graphite particles of Example 2.

[0302] It should be noted that the cumulative pore volume of Examples 1, 2, Comparative Examples 1 and 2 is less than 0.080 ml / g.

[0303] The carbon materials containing graphite particles manufactured in Examples 1, 2, 1, and 2 were evaluated as follows.

[0304] (Determination of physical properties of a single particle)

[0305] Using a micro compression testing machine MCT-510 manufactured by Shimadzu Corporation, a graphite particle contained in the carbon material produced in the examples and comparative examples was loaded vertically at a speed of 0.4462 mN / s, with a maximum test force of 9.81 mN. After reaching the maximum test force, the compressive stress and compressive displacement were measured when the load was unloaded to 0.05 mN at an unloading speed of 0.4462 mN / s.

[0306] The displacement rate at which the maximum test force is reached is obtained by dividing the particle size at which the maximum test force is reached by the particle size before the pressure is applied.

[0307] The compressive modulus is the value obtained by dividing the compressive stress (= displacement of the particle size at the observation point / particle size of a graphite particle observed under a microscope before compression) from the maximum test force or the plateau region observed in the curve to the point before the plateau region. The average value calculated for three particles is recorded in Table 1.

[0308] The recovery rate is set as the value obtained by dividing the displacement of the particle size observed when the maximum test force is unloaded to 0.05 mN by the displacement of the particle size when the maximum test force is reached. The average value calculated for the three particles is recorded in Table 1.

[0309] (Method for determining Raman R value)

[0310] The carbon material manufactured in the examples and comparative examples was filled into the Raman spectrometer measuring container by naturally falling into it. The measuring container was irradiated with an argon ion laser (wavelength 514.5 nm), and the measuring container was rotated in a plane perpendicular to the laser while the Raman spectrum was measured to determine the Raman R value.

[0311] (Making the negative electrode)

[0312] 4.875 parts by mass of silicon with an average particle size of 5 μm, 92.625 parts by mass of carbon material prepared in the examples and comparative examples, 150 parts by mass of 1% aqueous solution of CMC (1.5 parts by mass of solids), 2.2 parts by mass of 45% aqueous dispersion of SBR (1 part by mass of solids), 1.86 parts by mass of 2.14% CNT / 3.21% CMC dispersion, and 50 parts by mass of water were added and kneaded using a mixer to obtain a slurry.

[0313] The obtained slurry was measured at a unit area weight of 7–8 mg / cm². 2 The active material is coated onto a 20 μm thick copper foil, which serves as the current collector, and then dried. The active material layer is then coated with a solution at a density of 1.45–1.55 g / cm³. 3 The method involves using a 250mmΦ roller press with a load sensor to roll and punch out a circle with a diameter of 12.5mm. The circle is then vacuum dried at 120℃ for 12 hours to obtain the negative electrode for evaluation.

[0314] (Making of a coin battery)

[0315] The obtained negative electrode and the lithium foil serving as the counter electrode are overlapped through a membrane impregnated with electrolyte to obtain a battery for charge-discharge testing. The electrolyte is prepared by dissolving LiPF6 in a mixture of ethylene carbonate / ethyl methyl carbonate / ethylene monofluorocarbonate = 30 / 60 / 10 (volume ratio) to achieve a concentration of 1 mol / L.

[0316] First, at 0.08 mA / cm 2 The battery was charged at a current density to a voltage of 5mV for the charge-discharge test, and then charged at a constant voltage of 5mV to a current value of 0.03mA / cm. 2 After lithium is doped into the negative electrode, the efficiency is 0.2 mA / cm 2 The battery was discharged at a current density until its voltage reached 0.7V (initial first cycle). Then, the charging current density was set to 0.2mA / cm². 2 The discharge current density is set to 0.3 mA / cm². 2 In addition, the charging and discharging were repeated four times under the same conditions as described above (the second to third cycles). "Charging" refers to the flow of current in the negative electrode of the evaluation towards the direction of lithium doping, and "discharging" refers to the flow of current from the negative electrode of the evaluation towards the direction of lithium dedoping.

[0317] Regarding the initial discharge capacity (mAh / g), the mass of the negative electrode active material is calculated by subtracting the mass of the copper foil cut to the same area as the negative electrode from the mass of the negative electrode, and the discharge capacity of the initial third cycle is divided by the mass of the negative electrode active material.

[0318] The charge / discharge efficiency for the first and third cycles is set as the ratio of discharge capacity to charge capacity in the first and third cycles ((discharge capacity / charge capacity) × 100).

[0319] The evaluation results are shown in Table 1 below.

[0320] [Table 1]

[0321] As can be seen from Examples 1 and 2, and Comparative Examples 1 and 2, graphite particles with mechanical properties as per the design guidelines can be manufactured, resulting in excellent battery characteristics of the specified carbon material. It should be noted that the individual particles in Comparative Example 2 exhibit a plateau region in their mechanical properties curves.

[0322] Those skilled in the art will obviously conceive of various modifications or alterations within the scope of the claims, and it should be understood that these also fall within the technical scope of this invention. Furthermore, the constituent elements of the above embodiments can be combined arbitrarily without departing from the spirit of the invention.

[0323] It should be noted that this application is based on Japanese patent application (Japanese Patent Application No. 2024-051879) filed on March 27, 2024, the contents of which are incorporated herein by reference.

Claims

1. A type of graphite particle coated with amorphous carbon, wherein, The value derived by dividing the displacement of the particle size observed when the particle was decompressed to 0.05 mN after being pressurized to 9.81 mN and then unloaded to 0.05 mN by the displacement of the particle size when it reached 9.81 mN is greater than 0.

5.

2. The graphite particles according to claim 1, wherein, When the particles are pressurized to a pressure of 9.81 mN, the mechanical curve does not include a plateau region.

3. The graphite particles according to claim 1, wherein, The compressive modulus of the particles is above 550 MPa when the particles are pressurized to a pressure of 9.81 mN.

4. The graphite particles according to claim 1, wherein, The displacement rate is less than 10% when the particles are pressurized to a pressure of 9.81 mN.

5. A carbon material comprising graphite particles according to any one of claims 1 to 4, The Raman R value of the carbon material is greater than 0.4 and less than 1.

0.

6. A carbon material comprising graphite particles according to any one of claims 1 to 4, The BET specific surface area of ​​the carbon material is 0.5 m². 2 / g or more and 3.0m 2 / g or less.

7. The graphite particles according to claim 1, wherein, The compressive modulus of the particles when they are pressurized to a pressure of 9.81 mN is greater than 150 MPa and less than 300 MPa.

8. The graphite particles according to claim 1, wherein, The displacement rate when the particles are pressurized to a pressure of 9.81 mN is greater than 4% and less than 10%.

9. A carbon material comprising graphite particles according to claim 1, 2, 7 or 8, The Raman R value of the carbon material is greater than 0.3 and less than 0.

4.

10. A carbon material comprising graphite particles according to claim 1, 2, 7 or 8, The BET specific surface area of ​​the carbon material is 0.5 m². 2 / g or more and 3.0m 2 / g or less.

11. A negative electrode material comprising: a carbon material containing graphite particles according to any one of claims 1 to 4 and Si-containing particles.

12. The negative electrode material according to claim 11, wherein, The negative electrode material also contains conductive additives.

13. A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is a negative electrode comprising graphite particles according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and method for manufacturing the same

    JP2023156005A

  • Crane operating system and operating method

    JP2024051879A